The crashworthiness performance of thin-walled ultralight braided lattice composite columns: Experimental and finite element study. (1st December 2020) - Abedi, Mohammad Mahdi; Jafari Nedoushan, Reza; Sheikhzadeh, Mohammad; Yu, Woong-Ryeol
Abstract: We studied the crashworthiness performance of thin-walled ultralight braided lattice composites (UBLCs) under quasi-static compressive loading experimentally and numerically. The lattice structures were initially preformed on mandrels with various cross-sectional geometries, including circular, octagonal, hexagonal, and rectangular. The effects of cross-section type and perimeter were also investigated. Our results showed that the square-shaped sample exhibited the highest specific absorbed energy (SAE) and absorbed energy per length. We also investigated the effect of the number of lattice layers. The concentric multi-layer samples absorbed more energy than single-layer samples due to interactions between the embedded layers. Furthermore, the crushing force efficiency (CFE) was improved by the use of multi-layer samples. Finite element (FE) modeling was used to predict and analyze the energy absorption behavior of UBLC samples. Both structure buckling and material failure were included in the simulations. The results of the FE simulation were in good agreement with our experimental results. The SAEs of single-layer and multi-layer UBLCs are significantly higher than those of expanded metal tubes. Considering SAE and CFE simultaneously, we can conclude that the energy absorption behavior of UBLC structures is more promising than that of similar tubular lattice structures.